Authentication using blockchain - Bose, Anindita; Islam, Raima; Safrina, Sikander Sofia; Bin Khurshid, Dishari; Khan, Mashequr Rahman (Brac University, 2023)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science, 2023.